Feasibility and sustainability analyses of carbon dioxide – hydrogen separation via de-sublimation process in comparison with other processes. (30th August 2019) - Yurata, Tarabordin; Lei, Hongwu; Tang, Liangguang; Lu, Meng; Patel, Jim; Lim, Seng; Piumsomboon, Pornpote; Chalermsinsuwan, Benjapon; Li, Chao'en
Abstract: Hydrogen (H2 ) plays a vital role both as a reactant in petrochemical processes and as an energy carrier and storage medium. When produced from carbon-containing feed stocks, such as fossil fuels and biomass, hydrogen is typically produced as a mixture with carbon dioxide (CO2 ), and must be subsequently separated by the associated energy, with an invertible energy penalty. In this study, the process for the removal of carbon dioxide from CO2 - H2 mixtures by de-sublimation was analysed. This process is particularly relevant to the production of liquid hydrogen (LH2 ) at cryogenic temperatures, for which cooling of the H2 stream is already necessary. The solid – gas equilibrium of CO2 - H2 was studied using the Peng-Robinson equation of state which provided a wide range of operating conditions for process simulation. The de-sublimation process was compared with selected conventional separation processes, including amine-based absorption, pressure swing adsorption and membrane separation. In the scenario in which the resulting products, carbon dioxide and hydrogen, were subsequently liquefied for transportation and storage at 10 bar and −46 °C, and 1 bar and −251.8 °C, respectively. The overall energy consumption per kg of CO2 separated (MJ/kgCO2), was found to follow the order: 8.19–11.21 for monoethanolamine (MEA) absorption; 1.81–8.93 for membrane separation; 1.53–5.69 for pressure swing adsorption; and 0.81–3.35 de-sublimation process. Each process was evaluated and compared on the bases of electricity demand, cooling water usage, high-pressure steam usage, and refrigeration energy requirements. Finally, the advantages and disadvantages were discussed and the feasibility and sustainability of the processes for application in the production of liquid hydrogen were assessed. Graphical abstract: Image 1 Highlights: Four approaches for CO2 - H2 separation were analysed. Energy consumptions follows: MEA absorption > membrane separation > PSA > de-sublimation. De-sublimation was proved having advantages when liquid as target products. The advantages and disadvantages, the feasibility and sustainability were assessed. Phase equilibrium analysis was conducted for a range of CO2 /H2 compositions.